Determinants of Generation Z's Muslim Fashion Behavior Intention in Banda Aceh City: Attitude Variables as Mediation - Dhiauddin Al Amiri; Novi Indriyani Sitepu; Khairil Umuri; Wirdah Irawati (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study aims to analyze the effect of Utilitarian Value and Hedonic Value on Behavior Intention, with Attitude as a mediating variable. Data collection was done through distributing questionnaires. The sample in this study was the Generation Z community in Banda Aceh City as many as 130 respondents, who were selected using the sampling technique according to Hair. The data analysis technique used in this research is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results showed that Utilitarian Value and Hedonic Value had a significant effect on Attitude partially. However, Utilitarian Value and Hedonic Value have no partial effect on Behavioral Intention, then Attitude has a significant effect on Behavioral Intention, while the mediating role of the Attitude variable mediates the effect of Utilitarian Value on Behavioral Intention and also Attitude mediates the effect of Hedonic Value on Behavioral Intention. The results showed that Gen Z's Behavioral Intention in Banda Aceh City in choosing Muslim fashion is more dominantly influenced by their Attitude, compared to the direct influence of Utilitarian Value and Hedonic Value.